Interventions for prevention and treatment of trastuzumab-induced cardiotoxicity: an umbrella review of systematic reviews and meta-analyses - Wang, Yunfang; Xu, Jianguo; Xie, Yafei; Zhou, Dan; Guo, Mingyue; Qin, Yu; Yi, Kang; Tian, Jinhui; You, Tao (Frontiers in Pharmacology, 2024)
Background: Trastuzumab therapy for HER2-positive cancers is associated with cardiotoxicity. This umbrella review synthesizes evidence from systematic reviews and meta-analyses on cardioprotective interventions during trastuzumab treatment. Methods: A comprehensive search was conducted in PubMed, Embase, Cochrane Library, and Web of Science. Systematic reviews and meta-analyses examining cardioprotective interventions in patients receiving trastuzumab were included. The methodological quality was assessed using the AMSTAR-2 tool. Data on cardiac events, treatment interruptions, left ventricular ejection fraction (LVEF) changes, and exercise interventions were synthesized. Results: Ten systematic reviews met the inclusion criteria. Statins demonstrated the strongest cardioprotective effect (RR = 0.47, 95% CI: 0.26-0.84), potentially preventing more than half of cardiac events during trastuzumab therapy, followed by beta-blockers (RR = 0.61, 95% CI: 0.39-0.93). Beta-blockers and ACEIs effectively reduced treatment interruptions, enabling approximately 40% more patients to maintain treatment continuity (RR = 0.63, 95% CI: 0.47-0.86). Among non-pharmacological interventions, structured exercise programs showed significant benefits in preserving cardiac function, demonstrating meaningful improvements in resting LVEF (WMD = -3.27%, 95% CI: -5.86 to -0.68). Discussion: This review demonstrates that cardioprotective interventions, particularly statins and beta-blockers, significantly reduce the risk of cardiac complications during trastuzumab therapy. The positive impact on cardiac events and treatment interruptions suggests these interventions may enhance overall treatment efficacy by allowing more patients to complete their prescribed course. Conclusion: Evidence strongly supports the systematic implementation of cardioprotective strategies in clinical practice, particularly statins and beta-blockers, as part of routine care protocols for patients receiving trastuzumab therapy. These interventions demonstrate significant potential in preventing cardiac complications and maintaining treatment continuity. Further research should focus on optimizing personalized approaches and evaluating long-term outcomes.